Assessment of the Relationship between Average Educational Grading and First Experience of Open Book Exams among medical students in basic sciences stage - Seyed Mehran Hosseini (Kerman University of Medical Sciences, 2015)
Background & Objective: Open book exams with free access to resources are effective for the better understanding of concepts and achieving higher levels of Blooms taxonomy This study investigated the correlation of average educational grading with open book exam score and with deep information processing (DIP) The attitudes of medical students in basic sciences stage regarding open book exams were also reported   Methods: In this descriptive study the subjects were 34 medical students in their third semester The students were informed of the date and duration of the quiz issues in question multiplechoice form of questions and the main book source for quiz 2 weeks in advance However students were not aware of it as an open book exam until it was performed After completing the test a survey and DIP were conducted for students anonymously Data were presented in the form of descriptive statistics The ttest and the correlation of educational grading with OBE and with DIP scores were performed using SPSS software   Results: The mean age of students was 2485 ± 012 years Their average educational grading and the the quiz and the DIP scores were 154 ± 022 658 ± 033 and 745 ± 137 respectively There were no significant differences among genders in the above mentioned variables The Pearson coefficient of the average educational grading was not significantly for the quiz score (0272) and the DIP score (0258) Moreover 91% of students stated that understanding is an essential requirement for success in open book exams Only 3% of students stated that open book exams reduce the incentive to attend classes   Conclusion: The average educational grading of medical students in basic sciences stage based on routine quiz scores is not an appropriate index of success in open book exams and gaining a deep understanding of topics The open book exam experience may be effective in increasing their awareness of their weaknesses in understanding concepts reasoning and drawing connection between lessons